Solvent-free adhesive for electron beam curing flexible package and preparation method of solvent-free adhesive
By introducing 3-(methacryloyloxy)propyltrimethoxysilane and bihydroxy quaternary ammonium salts into solvent-free adhesives for electron beam curing flexible packaging as crosslinking components, the problem of poor cooking resistance is solved, and high adhesion and humidity resistance is improved. It is suitable for flexible packaging composite films in the food and pharmaceutical fields.
Patent Information
- Application Number
- CN202510722271.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-30
- Publication Date
- 2025-08-01
AI Technical Summary
The existing solvent-free adhesives for electronic beam curing flexible packaging have poor cooking resistance, resulting in a degradation of adhesive performance in high temperature and high humidity environments.
The terminal hydroxy hyperbranched polymer prepared with 3-(methacryloyloxy)propyltrimethoxysilane and bihydroxy quaternary ammonium salt is used as the crosslinking component, combined with polyurethane acrylate, crosslinking is achieved through electron beam curing, enhancing the adhesion of the coating film and the substrate and moisture-heat resistance.
It improves the cooking resistance and antibacterial properties of the coating film, enhances the hygiene and safety of the packaging, and has low viscosity, odor-free and VOC emissions, and is suitable for flexible packaging composite films in the food and pharmaceutical fields.
Smart Images

Figure BDA0005429730200000031 
Figure BDA0005429730200000101 
Figure BDA0005429730200000102
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of adhesives, and particularly relates to a solvent-free adhesive for electron beam curing of flexible packaging and a preparation method thereof. Background Art
[0002] At present, the research focus of solvent-free adhesives for flexible packaging is solvent-free radiation-cured polyurethane adhesives, which mainly refer to adhesives cured by ultraviolet light (UV) or electron beam (EB). The film-forming substance is generally a terminal acrylate-based polyurethane prepolymer. Due to no VOC emission, it is energy-saving and environmentally friendly, and has extremely high market application prospects.
[0003] For example, in the patent with the authorization announcement number CN110387208B, an electron beam-cured composite adhesive, a flexible packaging composite film and a preparation method thereof are disclosed. The raw materials are made of the following mass ratio: 30-50 parts of difunctional aliphatic polyurethane acrylate, 10-30 parts of difunctional polyester acrylate, 10-15 parts of acryloylmorpholine, 10-20 parts of N,N-dimethylacrylamide, 10-15 parts of organic-inorganic hybrid material, and 0.5-2 parts of silane coupling agent. This composite adhesive is cured by electron beam, with fast curing and can be instantaneously cured, but has poor retort resistance. In special environments of high temperature and high humidity, it is prone to hydrolysis, resulting in a significant decrease in bonding performance. Summary of the Invention
[0004] The first object of the present invention is to provide a solvent-free adhesive for electron beam curing of flexible packaging, so as to solve the problem of poor retort resistance of the existing solvent-free adhesive for electron beam curing of flexible packaging.
[0005] The second object of the present invention is also to provide a preparation method of the polyurethane resin in the above-mentioned electron beam-cured solvent-free adhesive.
[0006] The object of the present invention can be achieved by the following technical solutions:
[0007] A solvent-free adhesive for electron beam curing of flexible packaging, comprising the following raw materials in parts by weight:
[0008] 60-80 parts of polyurethane acrylate, 10-15 parts of crosslinking component, 20-40 parts of diluent, and 5-10 parts of auxiliary agent.
[0009] The crosslinking component is a terminal hydroxyl hyperbranched polymer prepared from 3-(methacryloyloxy)propyltrimethoxysilane and dihydroxy quaternary ammonium salt.
[0010] Further, the crosslinking component is prepared by the following steps:
[0011] Add 3-(methacryloyloxy)propyltrimethoxysilane, dihydroxy quaternary ammonium salt, hydroquinone, and p-toluenesulfonic acid into a reaction kettle. Under nitrogen protection, react at 140 °C with stirring under normal pressure and reduced pressure for 2 h respectively to obtain the first-generation product;
[0012] Continue to add 3-(methacryloyloxy)propyltrimethoxysilane and p-toluenesulfonic acid to the first-generation product. Under nitrogen protection, react at 140 °C with stirring under normal pressure and reduced pressure for 2 h respectively. Then add dihydroxy quaternary ammonium salt and p-toluenesulfonic acid, and react at 140 °C with stirring under normal pressure and reduced pressure for 2 h respectively to obtain the crosslinked component.
[0013] Using 3-(methacryloyloxy)propyltrimethoxysilane and dihydroxy quaternary ammonium salt as monomers, prepare a hydroxyl-terminated hyperbranched polymer containing siloxane structure, allyl structure, alkyl long chain, and quaternary ammonium salt structure.
[0014] Furthermore, the molar ratio of 3-(methacryloyloxy)propyltrimethoxysilane to dihydroxy quaternary ammonium salt is 4:9. The ratio of the molar amount of 3-(methacryloyloxy)propyltrimethoxysilane added for the first time to the molar amount added for the second time is 1:3, and the ratio of the molar amount of dihydroxy quaternary ammonium salt added for the first time to the molar amount added for the second time is 1:2.
[0015] Furthermore, the dosage of p-toluenesulfonic acid is 0.5% of the total mass of 3-(methacryloyloxy)propyltrimethoxysilane and dihydroxy quaternary ammonium salt. The ratio of the mass of p-toluenesulfonic acid added for the first time, the mass added for the second time, and the mass added for the third time is 1:3:4.
[0016] Furthermore, the dosage of hydroquinone is 0.1% of the total mass of 3-(methacryloyloxy)propyltrimethoxysilane.
[0017] Furthermore, the structural formula of the dihydroxy quaternary ammonium salt is as follows:
[0018]
[0019] Among them, R is C 12 -C 18 alkyl, X - is Cl - or Br - .
[0020] Furthermore, the dihydroxy quaternary ammonium salt is one or more of dodecyl methyl dihydroxyethyl ammonium bromide, dodecyl dihydroxyethyl methyl ammonium chloride, octadecyl methyl dihydroxyethyl ammonium bromide, and octadecyl dihydroxyethyl methyl ammonium chloride.
[0021] Furthermore, the polyurethane acrylate is mainly prepared by chemically reacting polyester polyol, polyisocyanate, and hydroxy ester.
[0022] Furthermore, the specific synthesis steps of the polyurethane acrylate are as follows:
[0023] Add the polyester polyol and polyisocyanate into a reaction kettle, control the molar ratio of NCO / OH in the system to be 1.05 - 1.25, and react at 80 °C for 2 h; then add hydroxyethyl acrylate, control the molar ratio of NCO / OH in the system to be 0.8 - 0.95, and react at 70 °C for 2 h to obtain the polyurethane acrylate.
[0024] Furthermore, the molecular weight of the polyester polyol is 1000 - 3000.
[0025] Furthermore, the polyisocyanate is one or a mixture of several of isophorone diisocyanate, hexamethylene diisocyanate, dicyclohexylmethane diisocyanate, and 1,6 - hexane diisocyanate.
[0026] Furthermore, the hydroxyethyl acrylate is one or a mixture of several of pentaerythritol triacrylate, hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl acrylate, hydroxypropyl methacrylate, and 4 - hydroxybutyl acrylate.
[0027] Furthermore, the diluent is one or a mixture of several of trimethylolpropane formal acrylate, dipropylene glycol diacrylate, tripropylene glycol diacrylate, 6 - hexanediol diacrylate, and trimethylolpropane triacrylate.
[0028] Furthermore, the auxiliary agent consists of an adhesion promoter and a wetting agent in a mass ratio of 1:1:3 - 5.
[0029] Furthermore, the adhesion promoter is acrylate phosphate with a functionality of 8, purchased from Zhongshan Qianyou Chemical Materials Co., Ltd., model: UV7424.
[0030] Furthermore, the adhesion promoter can also be a silane coupling agent, specifically any one or several of 3 - (methacryloyloxy)propyltrimethoxysilane, vinyltriethoxysilane, vinyltrimethoxysilane, vinyltris(b - methoxyethoxy)silane, and vinylphosphate esters.
[0031] Furthermore, the wetting agent is BYK - 2008 wetting and dispersing agent.
[0032] The preparation method of the above solvent - free adhesive for electron - beam - cured flexible packaging includes the following steps:
[0033] By weight, take the polyurethane acrylate, cross - linking component, diluent, and auxiliary agent, mix and stir evenly, and keep the material temperature between 16 - 30 °C during the stirring process.
[0034] The beneficial effects of the present invention:
[0035] 1. The present invention provides a solvent-free adhesive for electron beam curing of flexible packaging, which is an electron beam curing solvent-free adhesive with low viscosity, no odor, no VOCs emission, rapid curing, environmental friendliness, safety and easy use. By using the principle of electron beam curing, polymers are crosslinked and cured, with high curing degree, long storage time and fast curing speed, and it can be widely applied to flexible packaging composite films in the fields of food, medicine, etc.
[0036] 2. In the present invention, a hyperbranched polymer with terminal hydroxyl groups prepared by introducing 3-(methacryloyloxy)propyltrimethoxysilane and dihydroxy quaternary ammonium salt into a conventional polyurethane acrylate electron beam curing coating is used as a crosslinking component. Compared with the existing active components (acrylic acid, hydroxyethyl acrylate, pentaerythritol tetraacrylate), this crosslinking component not only contains unsaturated double bonds and can participate in crosslinking reactions, but also is rich in polar hydroxyl groups, which can improve the adhesion between the coating film and the substrate. In addition, the molecular chain of this crosslinking component contains many siloxane structures and alkyl long chains. Based on the properties of siloxane being heat-resistant and alkyl long chains being hydrophobic, it can effectively improve the moisture and heat resistance of the coating film, that is, the retort resistance. The quaternary ammonium salt structure in the crosslinking component can also endow the coating film with good antibacterial properties, which is beneficial to improving the hygienic safety of packaging and extending the shelf life of products.
[0037] 3. In the present invention, the crosslinking component is actually a hyperbranched polymer. Due to its unique three-dimensional spherical structure, it has rich active end groups and low viscosity, and plays a role in enhancing and toughening in the polyurethane acrylate electron beam curing coating. However, the dosage should be strictly controlled. If the dosage is too low, the crosslinking degree of the coating film will be low and the hardness will be low, resulting in poor scratch resistance. If the dosage is too high, the coating film will be over-crosslinked, with a large hardness and prone to cracking, which is not conducive to obtaining high-performance flexible packaging adhesives. Specific embodiments
[0038] Next, the technical solutions in the embodiments of the present invention will be clearly and completely described in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative efforts belong to the scope of protection of the present invention.
[0039] Preparation Example 1
[0040] A crosslinking component is prepared by the following steps:
[0041] Add 0.1 mol of 3-(methacryloyloxy)propyltrimethoxysilane, 0.3 mol of dodecylmethyldihydroxyethylammonium bromide, 0.1 g of hydroquinone, and 0.27 g of p-toluenesulfonic acid into a reaction kettle. Under nitrogen protection, react at 140 °C with stirring under normal pressure and reduced pressure for 2 h respectively to obtain the first-generation product;
[0042] Continue to add 0.3 mol of 3-(methacryloyloxy)propyltrimethoxysilane and 0.81 g of p-toluenesulfonic acid to the first-generation product. Under nitrogen protection, react at 140 °C with stirring under normal pressure and reduced pressure for 2 h respectively. Then add 0.6 mol of dodecylmethyldihydroxyethylammonium bromide and 1.1 g of p-toluenesulfonic acid. Under nitrogen protection, react at 140 °C with stirring under normal pressure and reduced pressure for 2 h respectively to obtain the crosslinked component.
[0043] Preparation Example 2
[0044] A crosslinked component is prepared through the following steps:
[0045] Add 0.1 mol of 3-(methacryloyloxy)propyltrimethoxysilane, 0.3 mol of octadecyldihydroxyethylmethylammonium chloride, 0.1 g of hydroquinone, and 0.29 g of p-toluenesulfonic acid into a reaction kettle. Under nitrogen protection, react at 140 °C with stirring under normal pressure and reduced pressure for 2 h respectively to obtain the first-generation product;
[0046] Continue to add 0.3 mol of 3-(methacryloyloxy)propyltrimethoxysilane and 0.875 g of p-toluenesulfonic acid to the first-generation product. Under nitrogen protection, react at 140 °C with stirring under normal pressure and reduced pressure for 2 h respectively. Then add 0.6 mol of octadecyldihydroxyethylmethylammonium chloride and 1.17 g of p-toluenesulfonic acid. Under nitrogen protection, react at 140 °C with stirring under normal pressure and reduced pressure for 2 h respectively to obtain the crosslinked component.
[0047] Preparation Example 3
[0048] A crosslinked component is prepared in the same way as Preparation Example 1, except that 3-(methacryloyloxy)propyltrimethoxysilane in Preparation Example 1 is replaced with the same molar amount of triethoxymethylsilane.
[0049] Preparation Example 4
[0050] A crosslinked component is prepared in the same way as Preparation Example 1, except that dodecylmethyldihydroxyethylammonium bromide in Preparation Example 1 is replaced with the same molar amount of 2,3-dihydroxypropyl-trimethylammonium chloride.
[0051] Example 1
[0052] A solvent-free adhesive for electron beam curing flexible packaging comprises the following raw materials in parts by weight:
[0053] 60 parts of polyurethane acrylate, 10 parts of the crosslinking component of Preparation Example 1, 20 parts of diluent, and 5 parts of auxiliary agent.
[0054] The specific synthesis steps of the polyurethane acrylate are as follows:
[0055] Add the polyester polyol and isophorone diisocyanate into the reaction kettle, control the molar ratio of n(NCO) / n(OH) in the system to be 1.05, and react at 80 °C for 2 h; then add pentaerythritol triacrylate, control the molar ratio of n(NCO) / n(OH) in the system to be 0.8, and react at 70 °C for 2 h to obtain the polyurethane acrylate.
[0056] The molecular weight of the polyester polyol is 3000.
[0057] The diluent is trimethylolpropane formal acrylate.
[0058] The auxiliary agent is composed of an adhesion promoter and a wetting agent in a mass ratio of 1:1:3.
[0059] The adhesion promoter is acrylate phosphate with a functionality of 8, purchased from Zhongshan Qianyou Chemical Materials Co., Ltd., model: UV7424.
[0060] The wetting agent is BYK-2008 wetting and dispersing agent.
[0061] The preparation method of the above solvent-free adhesive for electron beam curing flexible packaging includes the following steps:
[0062] By weight, take the polyurethane acrylate, crosslinking component, diluent, and auxiliary agent, add them into the stirring barrel, and stir at 300 r / min for 10 min. During the stirring process, keep the material temperature between 16 - 30 °C.
[0063] Example 2
[0064] A solvent-free adhesive for electron beam curing flexible packaging, comprising the following raw materials in parts by weight:
[0065] 70 parts of polyurethane acrylate, 12 parts of the crosslinking component of Preparation Example 2, 30 parts of diluent, and 8 parts of auxiliary agent.
[0066] The specific synthesis steps of the polyurethane acrylate are as follows:
[0067] Add the polyester polyol and hexamethylene diisocyanate into the reaction kettle, control the molar ratio of n(NCO) / n(OH) in the system to be 1.15, and react at 80 °C for 2 h; then add hydroxyethyl acrylate, control the molar ratio of n(NCO) / n(OH) in the system to be 0.9, and react at 70 °C for 2 h to obtain the polyurethane acrylate.
[0068] The molecular weight of the polyester polyol is 1000.
[0069] The diluent is dipropylene glycol diacrylate.
[0070] The additive is composed of an adhesion promoter and a wetting agent in a mass ratio of 1:1:5.
[0071] The adhesion promoter is acrylate phosphate with a functionality of 8, purchased from Zhongshan Qianyou Chemical Materials Co., Ltd., model: UV7424.
[0072] The wetting agent is BYK-2008 wetting and dispersing agent.
[0073] The preparation method of the solvent-free adhesive for electron beam curing flexible packaging includes the following steps:
[0074] By weight, take polyurethane acrylate, crosslinking component, diluent, and additive, add them to a stirring tank, and stir at 500 r / min for 20 min. During the stirring process, keep the material temperature between 16 - 30 °C.
[0075] Example 3
[0076] A solvent-free adhesive for electron beam curing flexible packaging includes the following raw materials by weight:
[0077] 80 parts of polyurethane acrylate, 15 parts of the crosslinking component of Preparation Example 2, 40 parts of diluent, and 10 parts of additive.
[0078] The specific synthesis steps of polyurethane acrylate are as follows:
[0079] Add the polyester polyol and dicyclohexylmethane diisocyanate to a reaction kettle, control the molar ratio of n(NCO) / n(OH) in the system to be 1.25, and react at 80 °C for 2 h; then add 2-hydroxyethyl methacrylate, control the molar ratio of n(NCO) / n(OH) in the system to be 0.95, and react at 70 °C for 2 h to obtain polyurethane acrylate.
[0080] The molecular weight of the polyester polyol is 2000.
[0081] The diluent is dipropylene glycol triacrylate.
[0082] The additive is composed of an adhesion promoter and a wetting agent in a mass ratio of 1:1:4.
[0083] The adhesion promoter is acrylate phosphate with a functionality of 8, purchased from Zhongshan Qianyou Chemical Materials Co., Ltd., model: UV7424.
[0084] The wetting agent is BYK-2008 wetting and dispersing agent.
[0085] The preparation method of the above solvent-free adhesive for electron beam curing flexible packaging includes the following steps:
[0086] By weight, take polyurethane acrylate, crosslinking component, diluent, and additive, add them into a stirring barrel, stir at 500 r / min for 20 min, and keep the material temperature between 16 - 30 °C during the stirring process.
[0087] Comparative Example 1
[0088] A solvent-free adhesive for electron beam curing flexible packaging, compared with Example 1, replaces the crosslinking component in Example 1 with the product prepared in Preparation Example 3, and the remaining raw materials, parameters, and preparation process are the same as those in Example 1.
[0089] Comparative Example 2
[0090] A solvent-free adhesive for electron beam curing flexible packaging, compared with Example 1, replaces the crosslinking component in Example 1 with the product prepared in Preparation Example 4, and the remaining raw materials, parameters, and preparation process are the same as those in Example 1.
[0091] Comparative Example 3
[0092] A solvent-free adhesive for electron beam curing flexible packaging, compared with Example 1, replaces the crosslinking component in Example 1 with acrylic acid, and the remaining raw materials, parameters, and preparation process are the same as those in Example 1.
[0093] Comparative Example 4
[0094] A solvent-free adhesive for electron beam curing flexible packaging, compared with Example 1, changes the 10 parts by weight of the crosslinking component in Example 1 to 9 parts by weight, and the remaining raw materials, parameters, and preparation process are the same as those in Example 1.
[0095] Comparative Example 5
[0096] A solvent-free adhesive for electron beam curing flexible packaging, compared with Example 3, changes the 15 parts by weight of the crosslinking component in Example 3 to 16 parts by weight, and the remaining raw materials, parameters, and preparation process are the same as those in Example 3.
[0097] Use the solvent-free adhesives for electron beam curing flexible packaging obtained in Examples 1 - 3 and Comparative Examples 1 - 3 to prepare flexible packaging films. The specific process is as follows:
[0098] First, pour the adhesives of each group into a glue storage barrel respectively. Set the temperature of the glue storage barrel to 40 °C, the temperature of the metering roller to 45 °C, the temperature of the glue transfer roller to 45 °C, the temperature of the coating roller to 45 °C, and the temperature of the compounding roller to 45 °C;
[0099] The outer film is placed on the first unwinding unit, the middle film is placed on the second unwinding unit, and the inner film is placed on the third unwinding unit. The first unwinding tension is 80N, the second unwinding tension is 70N, and the third unwinding tension is 80N. The gap between the metering rollers is 9mm, the viscosity measurement is 65%, the winding tension is 100N, and the coating amount on the inner and outer layers is 1.5g / m 2 , and the machine speed is 350m / min;
[0100] The composite film is cured by an EB electron beam curing machine with a voltage of 120KV and a total irradiation dose of 25KGY;
[0101] According to the standard disclosed in GB / T 21302-2007, the peel strength of the above composite structure in the test example is tested. The composite structure is PET12 / / AL7 / / PE70. After being steamed at 135°C for 3h, the peel strength is tested again. The results are shown in Table 1:
[0102] Table 1
[0103]
[0104] It can be seen from the test results in Table 1 that compared with the solvent-free adhesives obtained in Proportions 1-3, the adhesive prepared by the present invention has better bonding performance and steam cooking resistance.
[0105] Place each group of adhesives on a washed and dried polytetrafluoroethylene plate, scrape off the excess with a glass rod to form a uniform thin layer, and cure it with an EB electron beam curing machine with a voltage of 120KV and a total irradiation dose of 25KGY. Then, measure the pencil hardness of the coating according to GB / T 6739-2006 and test the antibacterial rate according to QB / T2591-2003. The preparation method of the bacterial suspension is as follows: Place Escherichia coli and Staphylococcus aureus in LB agar medium respectively, place the medium on a shaker at 37°C and 200r / min and shake for 24h, then pick single colonies into liquid medium for culture to obtain bacterial liquid. Dilute the bacterial liquid to 4.0×10 5 cfu / mL; Cut the adhesive film into 1cm×1cm and perform ultraviolet sterilization. Place the sterilized adhesive film in the diluted bacterial liquid and shake-culture it with a blank control group (the bacterial liquid does not contain the adhesive film and the bacterial liquid concentration is the same) on a shaker at 37°C and 220r / min for 24h. Then take the same amount of the cultured bacterial liquid and spread it on LB agar medium, seal it with sealing glue, and invert it in a constant temperature incubator at 37°C for 24h (37°C, 30r / min). Count the colonies on the culture media of the blank group bacterial liquid and the experimental group bacterial liquid with the adhesive film respectively, and calculate its antibacterial rate;
[0106] The test results are shown in Table 2:
[0107] Table 2
[0108]
[0109]
[0110] As can be seen from the test results in Table 2, the adhesive prepared in Comparative Example 3 has no antibacterial property. Compared with the solvent-free adhesives obtained in Proportions 1-5, the adhesive prepared by the present invention has better mechanical properties and antibacterial properties.
[0111] It should be noted that in this article, relational terms such as first and second are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any actual relationship or order between these entities or operations. Moreover, the term "comprising", "including" or any other variant thereof is intended to cover non-exclusive inclusion, so that a process, method, article or device comprising a series of elements not only includes those elements, but also includes other elements not expressly listed, or also includes elements inherent to such process, method, article or device.
[0112] Although the embodiments of the present invention have been shown and described, for those of ordinary skill in the art, it can be understood that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and spirit of the present invention. The scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A solvent-free adhesive for electron beam curing of flexible packaging, characterized in that, It comprises the following raw materials in parts by weight: 60 - 80 parts of polyurethane acrylate, 10 - 15 parts of crosslinking component, 20 - 40 parts of diluent, 5 - 10 parts of auxiliary agent; The crosslinking component is a hydroxyl - terminated hyperbranched polymer prepared from 3 - (methacryloyloxy) propyltrimethoxysilane and dihydroxy quaternary ammonium salt.
2. The solvent-free adhesive for electron beam curing of flexible packaging according to claim 1, characterized in that, The crosslinking component is prepared through the following steps: Add 3 - (methacryloyloxy) propyltrimethoxysilane, dihydroxy quaternary ammonium salt, hydroquinone, and p - toluenesulfonic acid into a reaction kettle. Under nitrogen protection, react at normal pressure and reduced pressure for 2 h respectively under stirring at 140 °C to obtain the first - generation product; Continue to add 3 - (methacryloyloxy) propyltrimethoxysilane and p - toluenesulfonic acid to the first - generation product. Under nitrogen protection, react at normal pressure and reduced pressure for 2 h respectively under stirring at 140 °C. Then add dihydroxy quaternary ammonium salt and p - toluenesulfonic acid, and react at normal pressure and reduced pressure for 2 h respectively under stirring at 140 °C to obtain the crosslinking component.
3. The solvent-free adhesive for electron beam curing of flexible packaging according to claim 2, wherein, The molar ratio of 3 - (methacryloyloxy) propyltrimethoxysilane to dihydroxy quaternary ammonium salt is 4:
9. The ratio of the molar amount of 3 - (methacryloyloxy) propyltrimethoxysilane added for the first time to the molar amount added for the second time is 1:3, and the ratio of the molar amount of dihydroxy quaternary ammonium salt added for the first time to the molar amount added for the second time is 1:
2.
4. The solvent-free adhesive for electron beam curing of flexible packaging according to claim 2, characterized in that, The dosage of p - toluenesulfonic acid is 0.5% of the sum of the masses of 3 - (methacryloyloxy) propyltrimethoxysilane and dihydroxy quaternary ammonium salt. The ratio of the mass of p - toluenesulfonic acid added for the first time, the mass added for the second time, and the mass added for the third time is 1:3:
4.
5. The solvent-free adhesive for electron beam curing of flexible packaging according to claim 2, wherein, The dosage of hydroquinone is 0.1% of the total mass of 3 - (methacryloyloxy) propyltrimethoxysilane.
6. The solventless adhesive for electron beam curing of flexible packaging according to claim 2, characterized in that, The dihydroxy quaternary ammonium salt is one or more of dodecyl methyl dihydroxyethyl ammonium bromide, dodecyl dihydroxyethyl methyl ammonium chloride, octadecyl methyl dihydroxyethyl ammonium bromide, and octadecyl dihydroxyethyl methyl ammonium chloride.
7. The solvent-free adhesive for electron beam curing of flexible packaging according to claim 2, wherein, The auxiliary agent is composed of an adhesion promoter and a wetting agent in a mass ratio of 1:1:3 - 5.
8. A preparation method of a solvent-free adhesive for electron beam curing of flexible packaging as described in any one of claims 1-7, characterized in that, It comprises the following steps: By weight, take polyurethane acrylate, crosslinking component, diluent, and auxiliary agent, mix and stir evenly. During the stirring process, keep the material temperature between 16 - 30 °C.
Citation Information
Patent Citations
An electron beam cured composite adhesive, a flexible packaging composite film, and their preparation method
CN110387208B
Cited By
Production process of EB cured food packaging composite film and product
CN121973458A